2011
DOI: 10.1149/2.090202jes
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method to Grow Ge Thin Films on Si by Electrochemical Deposition for Photonic Applications

Abstract: Germanium films several micrometers in thickness were electrochemically deposited on silicon wafers for the first time without catalysts and at room temperature from a solution containing Ge species that have been electrochemically dissolved from Ge target. The films were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. SEM images show that the deposited products presented different structures (Flower-like, spheres, and thin films) depending on the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The mechanism of the electrodeposition of Ge in HF is described in a previous work. 17 In this methodology, the production of heaxafluorogermanate ions resulted from oxidation state IV to II followed by reduction process to germanium metal; Ge (0) deposited on the surface of the silicon (cathode). 17 Fig .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of the electrodeposition of Ge in HF is described in a previous work. 17 In this methodology, the production of heaxafluorogermanate ions resulted from oxidation state IV to II followed by reduction process to germanium metal; Ge (0) deposited on the surface of the silicon (cathode). 17 Fig .…”
Section: Resultsmentioning
confidence: 99%
“…17 In this methodology, the production of heaxafluorogermanate ions resulted from oxidation state IV to II followed by reduction process to germanium metal; Ge (0) deposited on the surface of the silicon (cathode). 17 Fig . 1 shows the SEM images and EDX spectra of Ge electrochemically deposited samples on Si at different current densities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36,[41][42][43][44][45][46] Ge electroplating has also been reported on semiconducting substrates such as Si. 47 There are some reports on the formation of thick Ge nanostructures, [48][49][50] which showed that, depending on potential, Ge nanostructures can be grown from aqueous solution by dissolution into and saturation of a liquid Hg electrode.…”
mentioning
confidence: 99%